Pengenalan Pentingnya Literasi Keuangan Bagi Para Guru - Nurbaeti Nurbaeti; Erika Astriani Aprillia; Novi Akhsani; Wiwit Setyawati; Ambarwati Ambarwati (Abdimisi, 2020)
Financial literacy is a basic need for avoiding financial distress. Financial distress is not only a function of low income, financial distress can also arise if there is an error in financial management (mismanagement) such as poor credit management and absence of financial planning. Therefore, upgrading the ability to know financial literacy is needed in order to succeed in managing funds and reducing consumptive behavior and pushing groups towards investing behavior. This PKM is in collaboration with SD Islam Al Azhar 17 Bintaro, South Tangerang. The purpose of this PKM is to increase knowledge about financial literacy for the teachers of SD Islam Al Azhar 17 Bintaro. Teachers are an extension of the hands of academics to reach more parties in order to familiarize the financial literacy movement in society. Training and socialization through webinars attended by 33 teachers of SD Islam Al Azhar 17 Bintaro on December 7, 2020. The results of PKM are 51.5% currently have basic knowledge of financial management. This PKM is expected to provide benefits for teachers, the community, OJK, the financial services industry, the government and academics.